2020
DOI: 10.1002/anie.202003685
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Kinetic Inertness for a Mn2+‐Bispidine Chelate: A Novel Structural Entry for Mn2+‐Based Imaging Agents

Abstract: The search for more biocompatible alternatives to Gd 3+-based MRI agents,a nd the interest in 52 Mn for PET imaging call for ligands that form inert Mn 2+ chelates.G iven the labile nature of Mn 2+ ,h igh inertness is challenging to achieve.The strongly preorganized structure of the 2,4-pyridyldisubstituted bispidol ligand L 1 endows its Mn 2+ complex with exceptional kinetic inertness.I ndeed, MnL 1 did not showa ny dissociation for 140 days in the presence of 50 equiv.o fZ n 2+ (37 8 8C, pH 6), while recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(114 citation statements)
references
References 34 publications
3
111
0
Order By: Relevance
“…One of the most widely explored alternatives relies on the use of high-spin Mn(II) complexes, which present similar abilities to enhance 1 H relaxation of water nuclei as analogous Gd(III) complexes [10][11][12]. The main challenge to develop Mn(II)-based contrast agents relies on the difficulties to obtain thermodynamically stable and kinetically inert complexes, to avoid the release of the potentially toxic metal ion [13], while leaving a coordination position available for a water molecule [14]. The inner-sphere water molecule exchanges with bulk water, which provides an efficient mechanism for the relaxation of water 1 H nuclei in the vicinity of the agent [15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely explored alternatives relies on the use of high-spin Mn(II) complexes, which present similar abilities to enhance 1 H relaxation of water nuclei as analogous Gd(III) complexes [10][11][12]. The main challenge to develop Mn(II)-based contrast agents relies on the difficulties to obtain thermodynamically stable and kinetically inert complexes, to avoid the release of the potentially toxic metal ion [13], while leaving a coordination position available for a water molecule [14]. The inner-sphere water molecule exchanges with bulk water, which provides an efficient mechanism for the relaxation of water 1 H nuclei in the vicinity of the agent [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted previously that a rigid scaffold such as bispidine around the Mn 2+ ion endows the manganese complex with increased kinetic inertness and similar to 10 No data on apparent molar activities for 52g Mn-labeled complexes were found in the literature for other chelators discussed here for comparison. 10,36 Radiolabeling with [ 177 Lu]LuCl 3 Encouraged by the relatively high pM value (pLu ¼ 18.1), preliminary radiolabeling studies were done to investigate the complexation kinetics of the hexadentate chelator H 3 glyox with [ 177 Lu]LuCl 3 . Although Lu 3+ ion is a larger trivalent metal ion with an ionic radius of 86-103 pm and coordination number 6-9, 17 the mismatch with the cavity size of H 3 glyox is evident from the observed RCYs.…”
Section: Radiolabeling With [ 52 Mn]mnclmentioning
confidence: 99%
“…20 The most inert Mn(II) complex was recently described by É Tóth et al, which is a Mn(II) chelate formed with a 2,4-pyridyl-disubstituted bispidol ligand. 8 Our recent studies performed with trisubstituted cyclododecane derivatives have revealed greater conditional stability for [Mn(PCTA)]than for [Mn(DOTA)] 2-(at pH=7.4). 16 The kinetic inertness of [Mn(PCTA)]is sufficiently high to allow for further ligand modification, such as reduction of ligand denticity to allow the coordination of a water molecule to the metal ion.…”
Section: Introductionmentioning
confidence: 98%
“…Among the recently studied systems there are very few inert Mn(II) complexes. 8 Within the group of open-chain ligands, the rigid CDTA 9 and its derivatives (i.e. PyC3A) 10 or PhDTA 11 complexes (Chart 1) display the best features.…”
Section: Introductionmentioning
confidence: 99%